Hot Corrosion Behavior of (Gd0.9Sc0.1)2Zr2O7/YSZ Thermal Barrier Coatings Exposed to V2O5 + Na2SO4 Molten Salt - GUO Lei, XIN Hui (Cailiao Baohu)
For evaluating the corrosion resistance of (Gd0.9Sc0.1)2Zr2O7 coating to molten salt, a (Gd0.9Sc0.1)2Zr2O7/YSZ coating was prepared by air plasma spray. The hot corrosion behaviors of the coating in V2O5+ Na2SO4 molten salt at 700～1 000 ℃ for 2 h and 10 h were investigated. Results showed that the (Gd0.9Sc0.1)2Zr2O7 coating reacted obviously with V2O5+Na2SO4 molten salt, and the corrosive products were GdVO4 and t-ZrO2, which presented little relationship with hot corrosion temperature and time. When the corrosion temperature was 700 ℃ or 800 ℃, there remained a certain content of Na2SO4 on the coating surface. From the cross-section analysis of coatings after corrosion, the coating surface formed a reactive layer that could suppress the permeation of molten salt to a certain degree. However, with the increase of the corrosion temperature, the ability to form the reaction layer became weak so that some obvious trace of molten salt could be observed in the coating. Generally, (Gd0.9Sc0.1)2Zr2O7/YSZ coatings could still keep structure integrity after hot corrosion in the molten salt at 700～1 000 ℃. Corresponding to the Lewis acid-base rule, the reaction mechanism between molten salt and (Gd0.9Sc0.1)2Zr2O7 coating was proposed for clarifying the principle of the coating resisting to molten salt corrosion.